Abnormalities in the Fiber Composition and Capillary Architecture in the Soleus Muscle of Type 2 Diabetic Goto-Kakizaki Rats - Shinichiro Murakami; Naoto Fujita; Hiroyo Kondo; Isao Takeda; Ryusuke Momota; Aiji Ohtsuka; Hidemi Fujino (The Scientific World Journal)
Type 2 diabetes mellitus is linked to impaired skeletal muscle glucose uptake and storage. This study aimed to investigate the fiber type distributions and the three-dimensional (3D) architecture of the capillary network in the skeletal muscles of type 2 diabetic rats. Muscle fiber type transformation, succinate dehydrogenase (SDH) activity, capillary density, and 3D architecture of the capillary network in the soleus muscle were determined in 36-week-old Goto-Kakizaki (GK) rats as an animal model of nonobese type 2 diabetes and age-matched Wistar (Cont) rats. Although the soleus muscle of Cont rats comprised both type I and type IIA fibers, the soleus muscle of GK rats had only type I fibers. In addition, total SDH activity in the soleus muscle of GK rats was significantly lower than that in Cont rats because GK rats had no high-SDH activity type IIA fiber in the soleus muscle. Furthermore, the capillary diameter, capillary tortuosity, and microvessel volume in GK rats were significantly lower than those in Cont rats. These results indicate that non-obese diabetic GK rats have muscle fiber type transformation, low SDH activity, and reduced skeletal muscle capillary content, which may be related to the impaired glucose metabolism characteristic of type 2 diabetes.